1982
DOI: 10.1136/jnnp.45.8.734
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid oestrone in pseudotumour cerebri

Abstract: SUMMARY The concentration of oestrone in the cerebrospinal fluid (CSF) from obese young women with pseudotumour cerebri was much greater than predicted and found in normal subjects. Each woman with pseudotumour cerebri, and a high level of CSF oestrone and a CSF protein less than 0-2 g/l, had clinical improvement when treated with an 800 calorie/day diet and dexamethasone 2 mg/day.Increased oestrone production in adipocytes by the aromatisation of androstenedione may be the factor responsible for obesity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
2

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 8 publications
0
30
0
2
Order By: Relevance
“…The predilection of the disease for a particular gender would suggest that hormones may play a role in pathogenesis; however, previous studies into the role of oestrogens were inconclusive and have not been replicated. 14,15 It may be that the class of hormones that need further investigation are the androgens, as highlighted by this case report and the previous cases (Table 1), coupled with the observation that another androgen dysregulated condition, PCOS, shares a strikingly similar clinical phenotype. Furthermore, one study reports an increased incidence (58%) of PCOS in FTM patients prior to hormonal therapy.…”
Section: Discussionmentioning
confidence: 55%
“…The predilection of the disease for a particular gender would suggest that hormones may play a role in pathogenesis; however, previous studies into the role of oestrogens were inconclusive and have not been replicated. 14,15 It may be that the class of hormones that need further investigation are the androgens, as highlighted by this case report and the previous cases (Table 1), coupled with the observation that another androgen dysregulated condition, PCOS, shares a strikingly similar clinical phenotype. Furthermore, one study reports an increased incidence (58%) of PCOS in FTM patients prior to hormonal therapy.…”
Section: Discussionmentioning
confidence: 55%
“…With one exception, 40 most available data oppose excessive CSF formation 16,41 as a cause of pseudotumor cerebri. In this one exception, 40 the author used a mathematical calculation on data obtained from lumbar pressure monitoring using an infusion test in only three patients and noted an increased rate of CSF formation.…”
Section: Rate Of Csf Formationmentioning
confidence: 99%
“…In this one exception, 40 the author used a mathematical calculation on data obtained from lumbar pressure monitoring using an infusion test in only three patients and noted an increased rate of CSF formation. However, detailed numerical and clinical data from this study are not available for analysis, and using similar techniques, a later study on a much larger sample of patients 41 showed no evidence of increased CSF formation.…”
Section: Rate Of Csf Formationmentioning
confidence: 99%
“…Many theories exist on PTC's pathomechanism. The mainstream of clinical research link this disease to the water retention effect of estrogens on the central nervous system [5,6]. However, this theory is contradicted by reports of PTC occurrence in males or in females with Turner's syndrome [7,8].…”
Section: Discussionmentioning
confidence: 99%